2006
DOI: 10.1158/1078-0432.ccr-06-1352
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance Protein 2 Is an Important Determinant of Paclitaxel Pharmacokinetics

Abstract: Purpose: P-glycoprotein (P-gp; ABCB1) efficiently transports lipophilic amphipathic drugs, including the widely used anticancer drug paclitaxel (Taxol). We found previously that human multidrug resistance protein 2 (MRP2; ABCC2) also transports paclitaxel in vitro, and although we expected that paclitaxel pharmacokinetics would be dominated by P-gp, the effect of Mrp2 was tested in vivo. Experimental Design: We generated and characterized Mdr1a/1b/Mrp2 À/À mice, allowing assessment of the distinct roles of Mrp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
86
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 27 publications
4
86
1
Order By: Relevance
“…Using cells overexpressing mouse and human P-gp paclitaxel was classified as a strong substrate (Schellens et al, 2000;Bardelmeijer et al, 2002). These findings were confirmed using mdr1a/1b(Ϫ/Ϫ) mice (Lagas et al, 2006) and WT mice cotreated with the P-gp inhibitor cyclosporin A (van Asperen et al, 1998), which showed significantly higher …”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Using cells overexpressing mouse and human P-gp paclitaxel was classified as a strong substrate (Schellens et al, 2000;Bardelmeijer et al, 2002). These findings were confirmed using mdr1a/1b(Ϫ/Ϫ) mice (Lagas et al, 2006) and WT mice cotreated with the P-gp inhibitor cyclosporin A (van Asperen et al, 1998), which showed significantly higher …”
Section: Discussionmentioning
confidence: 81%
“…It has been demonstrated that knockout mice are a good model to study the influence of transport proteins on the pharmacokinetics of drugs (Schinkel et al, 1995(Schinkel et al, , 1997Lagas et al, 2006). To evaluate the relevance of the in vitro findings for the in vivo situation brain and plasma concentrations of sorafenib in mdr1a/1b(Ϫ/Ϫ) and wild-type (WT) mice were determined.…”
mentioning
confidence: 99%
“…We previously showed the value of knockout mice in studying the role of ABCB1 (P-glycoprotein, P-gp) and/or ABCC2 (multidrug resistance protein 2, Mrp2) in PTX pharmacokinetics (13,14). We further aimed to better understand the impact of the Oatp1a/1b transporters at different systemic exposure levels of the anticancer drugs PTX and MTX, by testing different dosages.…”
Section: ) As the Variousmentioning
confidence: 99%
“…Because we recently demonstrated that hepatobiliary excretion of paclitaxel in the mouse is almost exclusively dependent on Mrp2 (Lagas et al, 2006), we tried to stimulate biliary paclitaxel excretion in mice by the coadministration of either diclofenac or benzbromarone. However, we were unable to show any in vivo stimulation (J. S. Lagas and A. H. Schinkel, unpublished data).…”
Section: Downloaded Frommentioning
confidence: 99%
“…To date, several compounds, e.g., probenecid, sulfinpyrazone, and sulfanitran, have been shown to stimulate the MRP2-mediated transport of lipophilic amphipathic drugs (Huisman et al, 2002;Zelcer et al, 2003). Stimulation of MRP2-mediated transport can be of interest, because we recently demonstrated in vivo that Mrp2 is an important determinant for biliary excretion and thereby pharmacokinetics of the lipophilic amphipathic anticancer drug paclitaxel (Lagas et al, 2006 GlaxoSmithKline (Uxbridge, Middlesex, UK) kindly provided Elacridar (GF120918). The BCRP/Bcrp1 inhibitor Ko143 was described previously (Allen et al, 2002).…”
mentioning
confidence: 99%